Antenatal Depressive Symptoms and Breastfeeding: A Prospective Cohort Study - Yusuff, A.; Tang, L.; Binns, C.; Lee, Andy (Mary Ann Liebert Inc., 2015)
Introduction: Globally many women suffer from depression during pregnancy. This study investigated the impact of antenatal depressive symptoms on the duration of breastfeeding up to 6 months among women in Sabah, Malaysia. Subjects and Methods: A prospective cohort study of 2,072 women was conducted in Sabah during 2009-2010. Participants were recruited at 36-38 weeks of gestation and followed up at 1, 3, and 6 months postpartum. Depressive symptoms were assessed using the validated Malay version of the Edinburgh Postnatal Depression Scale (EPDS). Cox regression analyses were performed to determine the relationship between antenatal EPDS scores and cessation of breastfeeding before 6 months postpartum. Results: In total, 1,078 (52%) women with complete information on breastfeeding duration were included in the final sample. Approximately 99% of mothers were breastfeeding at discharge, and 87% of them continued to breastfeed at 6 months postpartum. Women with an antenatal EPDS score of 8 or above were twice more likely to stop breastfeeding before 6 months (adjusted hazards ratio=1.95; 95% confidence interval, 1.26, 3.01) than those who scored less than 4 on the EPDS. Conclusions: Depressive symptoms during pregnancy appeared to be associated with early breastfeeding cessation for mothers residing in Sabah.